Manejo de enfermería en artroplastia de cadera en el entorno familiar . - Moyon Guachi, Edison Paul (2024)
Hip arthroplasty is an orthopedic surgery that replaces the joint between the head of the femur and the acetabulum of the hip bone with an artificial implant or prosthesis, making the older adult group more vulnerable to suffering from arthritis-type diseases or fractures with significant displacement of the hips. bone fragments, which can hinder their repair and total functional recovery, therefore the present bibliographic review aims to describe the nursing management in post-surgical patients of hip arthroplasty surgery in the familiar surroundings. A descriptive, analytical study was carried out through a bibliographic review of 51 scientific articles such as Scielo, Redalyc, Dialnet, Elsevier, American Academy of Orthopedic Surgeons (AAOS), Recimundo and metasearch engines such as Google Scholar, available in free access in which it is addressed. said topic, where coincidences and discrepancies were identified in the authors' criteria regarding the needs of the patient and family, barriers and facilitators, best nursing practices for the optimal management of the patient with hip arthroplasty in the familiar surroundings. In the results of the research work, the physical and psychological needs that the patient endures during the recovery process were identified, on the other hand, the family members presented lack of knowledge about postoperative care for the prevention of complications due to the lack of education on the part of health personnel, in addition, it was determined that ineffective care, difficulty in accessing health services and communication barriers had an impact on adherence to treatment, while facilitators to optimize the implementation of nursing interventions were cognitive competencies, technological advances and telerehabilitation. In conclusion, the best nursing practices for optimal management in patients with hip arthroplasty are achieved from good hospital discharge planning, coordinating actions with other health professionals and home monitoring, to provide care in mobilization, administration of medications, pain control, prevention of infections and pressure ulcers and necessarily involving the family during the recovery process to guarantee physical, mental and social well-being.